Effect of Stirring and Static Heating on Fibrilization of Milk Whey Protein: A Processing Approach - G. Rathod; J. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2020)
When globular proteins such as whey proteins are converted to fibril structure, the functional properties, including viscosity and water holding capacity, are improved. Consequently, they can be used as functional ingredients in a variety of foods such as yogurt and bakery products. In this study, milk whey protein isolates were converted to fibrils by heating at low pH using two different approaches to reduce fibrilization time without compromising the quality of fibrils. Fibrils were made with an intervention of stirring to reduce fibrilization time. Continuous stirring improved the quality of fibrils and speed of the fibrilization.
Keywords: milk whey proteins; fibrils; static heating; and stirring heating